Books of pets:Five classic tales from the master of animal adventures - King Smith,Dick (London: Penguin Random House UK, 2017)
Dick King-Smith$1 (Bs Book of Pets: Five Classic Tales from the Master of Animal Adventures is a charming collection of five short stories that celebrate the special bond between humans and their animal companions. Known for his warmth and insight into the animal world, King-Smith presents four previously published stories along with a brand-new, never-before-seen tale. Each story features a different pet, from a clever guinea pig and a royal corgi to a brave little mouse and a chick longing to be a duck. These tales gently explore themes of friendship, identity, empathy, and the joys and challenges of caring for animals. With his signature mix of gentle humor and heartfelt storytelling, King-Smith encourages young readers to appreciate the value of kindness and responsibility toward pets. Ideal for children aged 6 to 8, this anthology is perfect for reading aloud and is accompanied by simple pet-care insights woven naturally into each narrative. The Book of Pets is a delightful read for animal lovers, families, and fans of King-Smith$1 (Bs beloved classics like The Sheep-Pig and Harry$1 (Bs Mad.s
Book of Pets is a heartwarming anthology that brings together five engaging animal stories by celebrated children$1 (Bs author Dick King-Smith, known for his deep love of animals and storytelling talent. This collection includes four previously published tales and one brand-new story, each centered on a different pet with its own unique personality and adventure. Written in a simple, accessible style ideal for young readers, the book not only entertains but also imparts gentle lessons about empathy, responsibility, and the special relationship between people and their pets. It reflects King-Smith$1 (Bs trademark blend of imagination, humor, and affection for animals, making it a delightful and educational read for children and a nostalgic treat for parents and educators.s
Keywords: Human-animal relationships; Animal stories